Decrease of PCDD/F Levels in Human Blood—Trend Analysis for the German Population, 1991–1996 - Wittsiepe, Jürgen; Schrey, Petra; Ewers, Ulrich; Wilhelm, Michael; Selenka, Fidelis (Environmental research, 2000)
More than 500 whole blood samples of normal subjects from Germany collected in 1991–1996 have been analyzed for polychlorinated dibenzo-p-dioxins (PCDD) and dibenzofurans (PCDF) by capillary gas chromatography/high-resolution mass spectrometry. Over the examined time period a continuous decrease of the PCDD/F concentrations in human blood was observed. The mean levels found were about 42.7 pg I-TEq/g (lipid basis) in 1991 and 20.7 pg I-TEq/g (liquid basis) in 1996 {median: 40.8 and 19.2}. A reduction to about half was found for most congeners. Each 1-year subset of the entire collective shows a positive correlation of the PCDD/F blood levels with age for most of the congeners, the sum values, and the calculated toxicity equivalents. For statistical evaluation a multiplicative model was used: Concentration in blood=A.ageB. The correlation is mostly pronounced for lower chlorinated PCDD and for 2,3,4,7,8-PentaCDF.